A educação moral e cívica do regime militar brasileiro, 1964-1985: a filosofia do controle e o controle da filosofia - Wilson Francisco Correia (EccoS – Revista Científica)
During the Brazilian military regimen (1964-1985) the philosophy was neglected in benefit of the moral and civic education. In the period, it invigorated a philosophy of the control established in the repression for the violence and the ideology of persuasions of the national consciences favorable to the authoritarian regimen, reason for which if it made necessary then the control of the philosophy. On the basis of this historical fact, the present study, carried through according to of research rules of the bibliographical-documentary research, displays and analyzes some aspects of this thematic one. The result the one that arrives is that the exclusion of the philosophy of the Brazilian schools during the military regimen in serves them of example to be observed, so that today, when the philosophy comes back to be obligator, not to run the risk to see its curricular citizenship one more time spoiled.